Cephalometric evaluation of soft palate changes after maxillary advancement in lip and palate cleft patients - Kamal Qaranizade; Alireza Jafari; Mona Farahmand; Hamidreza Mahaseni Aghdam; Leila Talebzade Shooshtari (Wolters Kluwer Medknow Publications, 2021)
Introduction: Changes in the soft palate and velopharyngeal function are among the most important concerns for maxillofacial surgeons in patients with midface deficiency, especially in those with cleft palate who needed maxillary advancement. In this study, we evaluated cephalometric changes in soft palate after maxillary advancement. Materials and Methods: This study included 16 cleft patients (7 females and 9 males), with a mean age of 22 ± 3.47. The maxillary advancement alone was done in 10 patients and bimaxillary osteotomy in the other six patients. Cephalometric characteristics were assessed before and 6 months after the surgery, and the results were analyzed using paired t-test or Wilcoxon test. Results: The results showed a 6% increase (P < 0.05) for PNS-U (soft palate length) index. In addition, PTM-UPW (upper pharyngeal space) and U-MPW (middle pharyngeal space) increased by 5% (P < 0.05) and 5% (P < 0.08), respectively, after the surgery. V-LPW (lower pharyngeal space) also increased by 0.6% but was not statically significant. Conclusions: According to the results of this study, after surgical maxillary advancement, changes were observed in upper and middle pharyngeal spaces, soft palate length, and inclination, but lower pharyngeal space remained unchanged.